Telaah Sadd Adz-Zariah PRISONER RELEASE POLICY DURING COVID-19 FROM SADD AL-ŻARĪ'AH'S PERSPECTIVE - Arisva, Vatta; Mahdi, M. Fakhrul (Al-Risalah, 2023)
The policy of the Minister of Law and Human Rights regarding granting prisoner release at the beginning of 2020 has caused a stir among the public because this policy was issued in the midst of the country being hit by the COVID-19 pandemic, a symptom of a deadly disease. On this basis, the researcher wanted to find out how to grant prisoner release based on the policy of the Minister of Law and Human Rights in the midst of the Covid-19 pandemic?, and what is Sadd al-żarī'ah's study of prisoner release based on the policy of the Minister of Law and Human Rights during Covid-19? This qualitative research used a normative method and a statute approach. Meanwhile, the types of data used were secondary data and primary data. The results of this research showed that the granting of prisoner release was carried out by Correctional Institutions with an integrated Correctional Database System (CDS) for prisoners who had fulfilled the substantive and administrative requirements by going through the procedures process. The policies were reviewed through sadd al-żarī'ah, which was a method of carrying out the law. In this case, seeing the intermediary of the action could lead to maslahah or mafsadat. The greater benefit arising from this policy is protecting lives by preventing the transmission of COVID-19, which could be deadly in Correctional Institutions as closed housing and over capacity. However, there are also consequences in the form of repetition of criminal acts (recidivism) by prisoners.